Calculus Concepts: An Informal Approach to the Mathematics of Change 5th Edition

Published by Brooks Cole
ISBN 10: 1-43904-957-2
ISBN 13: 978-1-43904-957-0

Chapter 3 - Determining Change: Derivatives - 3.7 Activities - Page 244: 14


$$\lim _{x \rightarrow 4} \frac{x-4}{(x+4)^{0.3}-2} =0$$

Work Step by Step

Given $$\lim _{x \rightarrow 4} \frac{x-4}{(x+4)^{0.3}-2}$$ using the method of replacement \begin{align*} \lim _{x \rightarrow 4} \frac{x-4}{(x+4)^{0.3}-2} &=\lim _{x \rightarrow 4} \frac{4-4}{(4+4)^{0.3}-2}\\ &=\lim _{x \rightarrow 4} \frac{0}{(8)^{0.3}-2}\\ &=0 \end{align*}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.